Tuberculosis and parenteral viral hepatitides: incidence of mixed forms - A. A. Asratyan; D. V. Solovyev; E. V. Rusakova (Туберкулез и болезни лёгких)
Objective: to estimate the frequency of parenteral viral hepatitides (HB and HC) (PVH) in patients with tuberculosis in Moscow in relation to data on their incidence in the aggregate population of the capital.Materials and methods. The authors analyzed the incidence of (acute, chronic) HB and HC (carriage) and tuberculosis in Moscow in 2009. A total of 24,220 cards for infectious patients (No. 089/y) and federal statistical follow-up forms (No. 2) were first processed to compare and search for personal data among the patients with tuberculosis and all forms of PVH and to establish the evidence of PVH and tuberculosis comorbidity.Results. The infection of tuberculosis patients with parenteral hepatitis B and C viruses was ascertained to be 5.5 to 284.9 times higher (in relation to the form of a hepatitis course) than that in the aggregation population of Moscow, which suggests that PVH is of high significance for the tuberculosis patients and that it is necessary to improve a PVH prevention program among this cohort patients. Analysis of the sex-age structure shows that male tuberculosis patients in the 20-39-year-old group should be considered to be a special risk group that should attract special attention when implementing preventive measures. The tuberculosis mortality rate among mixed infected patients was 1.8-fold higher than among those who had PVH-uncomplicated tuberculosis.Conclusion. The results of the investigations are suggestive of the evidence of PVH and tuberculosis comorbidity. The mixed forms of these infections in different combinations have been established to be accompanied by their severer clinical course and high death rates.